2014
DOI: 10.1080/1068316x.2014.915325
|View full text |Cite
|
Sign up to set email alerts
|

The influence of defendant race and victim physical attractiveness on juror decision-making in a sexual assault trial

Abstract: Previous research has examined separately the influence of defendant race and victim physical attractiveness on juror decision-making in sexual assault trials. The current study sought to examine the combined effects of defendant race and victim physical attractiveness in a trial of alleged acquaintance sexual assault. Mock jurors read a trial transcript in which the defendant race and victim physical attractiveness were manipulated via photographs. Results demonstrated that women were not influenced by victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…Research has shown that when defendant and victim race are manipulated in a sexual assault case, the participants rated defendants as more guilty on a 7 point scale of subjective guilt when the defendant was Aboriginal Canadian as opposed to White Canadian (Pfeifer & Ogloff, 2003). Furthermore, Aboriginal Canadian defendants receive harsher sentence recommendations than White or Black defendants (Maeder, Yamamoto, & Saliba, 2015). In Canada, there has been some examination of which stereotypes exist (Corenblum & Stephan, 2001), how they might influence juror decision making (Maeder, Yamamoto, McManus & Capaldi, 2016), and how race salience moderates this effect (Maeder, Yamamoto & McManus, 2015), but this research is relatively new and only beginning to broach this topic.…”
Section: Defendant Racementioning
confidence: 99%
“…Research has shown that when defendant and victim race are manipulated in a sexual assault case, the participants rated defendants as more guilty on a 7 point scale of subjective guilt when the defendant was Aboriginal Canadian as opposed to White Canadian (Pfeifer & Ogloff, 2003). Furthermore, Aboriginal Canadian defendants receive harsher sentence recommendations than White or Black defendants (Maeder, Yamamoto, & Saliba, 2015). In Canada, there has been some examination of which stereotypes exist (Corenblum & Stephan, 2001), how they might influence juror decision making (Maeder, Yamamoto, McManus & Capaldi, 2016), and how race salience moderates this effect (Maeder, Yamamoto & McManus, 2015), but this research is relatively new and only beginning to broach this topic.…”
Section: Defendant Racementioning
confidence: 99%
“…Unfortunately, irrelevant, extralegal factors such as attractiveness and gender often affect jurors' decisions in the courtroom (Mazzella & Feingold, 1994;McKimmie, Newton, Terry, & Schuller, 2004). Specifically, researchers have identified race as a variable influencing jurors' courtroom perceptions (Devine & Caughlin, 2014;Jones & Kaplan, 2003;Maeder & Burdett;Maeder, Yamamoto, & Saliba, 2015).…”
Section: List Of Figuresmentioning
confidence: 99%
“…Initial experimental research has also indicated that prospective jurors discriminate against Aboriginal defendants in certain crime scenarios (Maeder & Burdett, 2013;Maeder et al, 2015).…”
Section: List Of Figuresmentioning
confidence: 99%
See 2 more Smart Citations